Global prevalence and epidemiological trends of Hashimoto's thyroiditis in adults: A systematic review and meta-analysis - Hu, Xiaojie; Chen, Yuquan; Shen, Yiting; Tian, Rui; Sheng, Yuqin; Que, Huafa (Frontiers in Public Health, 2022)
Objective: Hashimoto's thyroiditis is associated with cardiovascular disease and malignancy, but the global status of Hashimoto's thyroiditis is not well characterized across regions. Our objective was to assess the prevalence and trends of Hashimoto's thyroiditis in adults in different economic income regions around the world. Methods: For this systematic review and meta-analysis, we searched PubMed, Embase, MEDLINE, Scopus, and Web of Science databases, and finally included 48 representative studies. For this systematic review and meta-analysis, we searched databases such as PubMed, Embase, MEDLINE, Scopus, Web of Science, etc., from the inception of the library to June 2022, without language restrictions. Finally, 48 representative studies were included for random-effects meta-analysis to obtain the overall prevalence of Hashimoto's thyroiditis in adults worldwide. We stratified by time of publication, geographic region, economic level of the region of residence, gender, diagnostic method, etc. Results: A total of 11,399 studies were retrieved, of which 48 met the research criteria: 20 from Europe, 16 from Asia, 5 from South America, 3 from North America, and 3 from Africa There are 2 projects involving 19 countries and 22,680,155 participants. The prevalence of Hashimoto's thyroiditis was 7.5% (95%CI 5.7 - 9.6), in the low-middle-income group the prevalence was 11.4% , the upper-middle-income group, the prevalence was 5.6%, and in the high-income group, the prevalence was 8.4%. The prevalence of Hashimoto's varied by geographic region: Africa (14.2%), Oceania (11.0%), South America and Europe 8.0%, 7.8% in North America, and 5.8% (95%) in Asia. Although our investigator heterogeneity was high , our results using a sensitivity analysis showed robustness and reliability of the findings. People living in low-middle-income areas are more likely to develop Hashimoto's thyroiditis, people in high-income areas are more likely to develop Hashimoto's thyroiditis than people in upper-middle-income areas, and women's risk is about four times higher than men's. Conclusions: In low-middle-income areas, the prevalence of Hashimoto's thyroiditis is high, so local health departments should take strategic measures to prevent, detect, and treat Hashimoto's thyroiditis. At the same time, the hidden medical burden caused by other diseases caused by Hashimoto's thyroiditis should also be done well.